Investment climate of Georgia after Rose Revolution: Recent improvements and new challenges - Tea Kbiltsetskhlashvili (IBSU Scientific Journal (IBSUSJ), 2008)
The article focuses on effectiveness of Investment climate in Georgia after transition period. Investment climate is the institutional, policy and regulatory environment in whichfirms operate - factors that influence the link from sowing to reaping and I can say that investment climate itself is the process from sowing to reaping because you will reap what you sew. Investment climate is the opportunity and incentive for firms to invest productively, create jobs and expand. One of the major determinations of country s economic developments and wellbeing are the indicators of investment structure and volume These indicators show attractiveness of economy for foreign investors and give clues for analyzing countries development process. Investment climate matters for the total factor productivity, average wage rates, the rate of return on fixed assets, growth rate of output, employment, corruption plus government regulations, taxes, political and economical stability, migration. A good investment climate is an essential pillar of a country s strategy to stimulate economic growth, which in turn generates opportunities for poor people to have more productive jobs term effect of foreign investment will increased in increased employment and household income, poverty will be decreased and Georgian economy will be developed. The paper also includes the results of a survey conducted to find out the changes of investment climate after Rose Revolution.
Keywords: 330; foreign direct investment; natural resources; employment; economic growth; political stability; taxes; corruption